TREATMENT OF GRANULOMATOUS EPULIS USING LASER - Novendy Yoyada; Dianty Saptaswari; Hansen Kurniawan; Onge Victoria Hendro (Dentino : Jurnal Kedokteran Gigi, 2023)
Background: Epulis is an epithelial tumor that is non-osteogenic. Epulis can be found in the oral cavity both on the gingiva and in the alveolar mucosa. Epulis is a benign enlargement of soft tissue. Granulomatous epulis is one type of epulis that is often found. This granulomatous epulis is a granulative tissue reaction with the characteristics of bleeding easily and having a reddish color. This epulis can disturb the patient both psychologically because there is a large mass in the oral cavity, causing it to be unaesthetic if it occurs in the anterior teeth area, disrupting the chewing process and even disrupting the speech process if it is in the posterior teeth.  Apart from causing discomfort to the patient, there are several types of epulis that can cause pain. Objective: To find out how to make a diagnosis of granulomatous epulis accompanied by treatment using a laser. Case: A 45 year old female patient came with complaints of enlarged gums since 1 year ago.  The patient initially used dentures, but currently the dentures cannot be used and the patient feels uncomfortable because he cannot chew food due to a large lump in the oral cavity. Case Treatment: At the first visit, an etiotropic phase is carried out in the form of elimination of local factors, then the patient is referred for supporting examinations in the form of panoramic radiography and FNA-B examination.  This examination functions to determine whether there is malignancy or not.  After the results showed no malignancy, we continued with the surgical phase in the form of excision of granulomatous epulis using a laser. Conclusion: Granulomatous epulis therapy using laser accompanied by removal of remaining tooth roots shows satisfactory therapeutic results. Keyword: Epulis, Epulis Granulomatosa, Excision, Laser